Accountability Forums and Dispute System Design. Issue 3 (1st February 2017) - Amsler, Lisa Blomgren; Sherrod, Jessica
ABSTRACT: The accountability literature refers to forums of accountability, including judicial and quasi-judicial forums. Administrative agencies enforce law and manage conflict, in part, through quasi-judicial processes, such as adjudication and dispute resolution. This is an arena of public management largely missing in the accountability literature. How is accountability defined, designed, and assessed for the quasi-judicial systems that manage conflicts or resolve disputes in public agencies? This article applies theories of accountability and justice to understand accountability as a mechanism and a virtue in quasi-judicial agency settings. Drawing from the Dispute System Design literature to introduce design principles that enhance accountability to these forums, it provides a framework to assess the accountability promise of justice in these forums and suggests a program for further research on accountability using theories of justice.